2010
DOI: 10.1177/0960327110361760
|View full text |Cite
|
Sign up to set email alerts
|

A crucial role of nitric oxide in acute lung injury secondary to the acute necrotizing pancreatitis

Abstract: To investigate the role of nitric oxide (NO) in acute lung inflammation and injury secondary to acute necrotizing pancreatitis (ANP), 5% sodium taurocholate was retrogradely injected into the biliopancreatic duct of rats to ANP model. These ANP rats were given L-Arginine (L-Arg, 100 mg/kg), L-NAME (10 mg/kg), or their combination by intraperitoneal injection 30 min prior to ANP induction. At 1, 3, 6, and 12 hours after ANP induction, lung NO production, and inducible NO synthase (iNOS) expression were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…One of the mechanisms that may contribute to pulmonary hypertension is the increase in isoprostane levels that we report here, because F 2 -isoprostanes are powerful constrictors in human pulmonary smooth muscle [42] and cause pulmonary vasoconstriction and hypertension in the rat lung [43,44]. Furthermore, extracellular Hb strongly upregulated inos in the lung, which would certainly contribute to the acute lung inflammation and damage associated with necrotizing pancreatitis as previously reported [45].…”
Section: Discussionsupporting
confidence: 74%
“…One of the mechanisms that may contribute to pulmonary hypertension is the increase in isoprostane levels that we report here, because F 2 -isoprostanes are powerful constrictors in human pulmonary smooth muscle [42] and cause pulmonary vasoconstriction and hypertension in the rat lung [43,44]. Furthermore, extracellular Hb strongly upregulated inos in the lung, which would certainly contribute to the acute lung inflammation and damage associated with necrotizing pancreatitis as previously reported [45].…”
Section: Discussionsupporting
confidence: 74%
“…These early and late inflammatory responses partially account for unsuccessful therapies in severe acute pancreatitis (24). Nitric oxide has also been implicated in the development of acute pancreatitis (26,27). Acute lung injury is the most common extrapancreatic complication of acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneal administration of L -NAME is a well-documented procedure [38,39,40], and the dosage utilized here was chosen based on previously published results to obtain a significant inhibition of NOS activity [38,39,40,41]. In particular, Cheng et al [39] demonstrated significantly attenuated NO production and NOS mRNA expression in rats treated with 10 mg/kg i.p.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Cheng et al [39] demonstrated significantly attenuated NO production and NOS mRNA expression in rats treated with 10 mg/kg i.p. L -NAME, a lower dosage than the one used in this study.…”
Section: Discussionmentioning
confidence: 99%